Integrated Online Dispute Resolution in Disputes Over National Health Insurance Claims: The Perspectives of the Rule of Law and The State of Power - Dessy Puspita Tjahjadi; Sri Redjeki Slamet; Ade Hari Siswanto (PT Publikasiku Academic Solution, 2026)
The National Health Insurance (Jaminan Kesehatan Nasional/JKN) program guarantees the right to healthcare; yet, claims disputes between hospitals and Badan Penyelenggara Jaminan Sosial (BPJS) Health expose persistent imbalances in their resolution. Despite normative pathways encompassing deliberation, mediation, and litigation, objections to claim verification are resolved internally by BPJS Health, while judicial recourse is rarely pursued even in the presence of substantial pending claims. This study analyses existing dispute resolution mechanisms through rechtsstaat and machtsstaat perspectives and formulates an integrated Online Dispute Resolution (ODR) model to ensure party equality and protect participants' rights. Employing a normative juridical method with statutory, case, conceptual, and comparative approaches alongside empirical searches of the Supreme Court Decision Directory the study draws on rule of law theory and Nonet and Selznick's responsive law theory. The findings indicate that the current mechanism falls short of substantive rechtsstaat standards and reflects machtsstaat residues, as the principle of nemo judex in causa sua is not fully upheld. The proposed integrated ODR model consolidates negotiation, mediation, clinical panel review, and arbitration into a single independent digital platform. Rather than creating new institutional authority, the model unifies mechanisms already recognized under Indonesian law into a more transparent, equitable, and accountable process, thereby restoring party parity and protecting participants' constitutional rights as a realization of substantive rechtsstaat.